Recent advances in renewable hydrogen production by thermo-catalytic conversion of biomass-derived glycerol: Overview of prospects and challenges - Ayodele B.V.; Abdullah T.A.R.B.T.; Alsaffar M.A.; Mustapa S.I.; Salleh S.F. (Elsevier Ltd, 2023)
Biodiesel; Biomass; Carbon dioxide; Catalytic reforming; Energy conservation; Glycerol; Oils and fats; Petroleum prospecting; Reforming reactions; Steam reforming; Catalytic conversion; Catalytic process; Global energy demand; Glycerol conversions; Glycerol production; Renewable hydrogen production; Renewable hydrogens; Technological route; Hydrogen production